Environmental compliance and practices of cruise ships in Iceland : an exploratory case study - port of Ísafjörður - Wang, Sheng-Ing, 1982- (2020)
Verkefnið er lokað til 31.12.2020. The drastic growth of cruise tourism in the world, while potentially beneficial for economic growth in local communities, can also bring many problems and concerns, especially regarding impacts to the environment. This research took the port of Ísafjörður, Iceland, a recent hotspot destination for cruise ships, as a case study for better understanding the potential environmental impacts from cruise ships. The study’s aims were: 1) to determine how much and what kind of waste generated from cruise ships had been discharged to the shore facilities in Ísafjörður in 2019, and 2) to explore the compliance behaviour of the ships in adhering to Icelandic and international environmental regulations. To do this, quantitative and qualitative questions were assessed by interviewing officers from 40 cruise ships, accounting for 87% of the total ships that docked and anchored in Ísafjörður in the 2019 cruise ship season. The interview questions were designed based on the convention of MARPOL and the law of Iceland, and these questions were compared with the ship’s statutory record or ship’s certificates to strengthen the reliability and correctness of the data. The interview questions covered five categories: emissions, waste oil, wastewater, garbage and food waste, and ballast water. Results showed that very little garbage and food waste had been discharged to shore facilities, and this was likely because Ísafjörður is one of several stops for many cruise ships in Iceland and the waste had simply been discharged elsewhere. However, in assessing the other four categories, eight out of 40 cruise ships carried out illegal activities, including 12 specific violation cases. This thesis discusses three primary possible reasons for those violations: accessibility, inconsistency, and monitoring, and then gives three examples of incentive for improving compliance behaviour in the cruise industry without imposing a law. Interested parties such as local communities, national decision makers, ...